Synthesis, characterization, and incorporation of upconverting nanoparticles into a dental adhesive - Rocha Pacheco, Rafael (2021)
The purpose of this study was to describe the synthesis, characterization, and functionalization of b-NaYF4:30%Yb/0.5%Tm upconverting nanocrystals for use as nanofillers in a dental adhesive and microscopically evaluate the interface between the particles and a commercial adhesive. The upconverting nanoparticles were synthesized and purified by thermal decomposition, and their chemical composition determined by energy dispersive X-Ray spectroscopy. The crystalline structure was characterized using X-Ray diffraction and morphology and size were observed with scanning and transmission electron microscopy. Upconverting emission was evaluated by spectrophotometry irradiating the particles with a 975 nm diode laser. Particles were functionalized with polyacrylic acid and the success was confirmed by measurement of Zeta Potential and transmission electron microscopy. The results of X-ray diffraction found a pure hexagonal phase crystalline pattern. Scanning electron microscopy showed uniform dispersion of hexagonal-shaped particles of approximately 150 nm. Upconversion emission was observed in 344 nm, 361 nm, 450 nm, 474nm, 646 nm, 803 nm. Functionalization success was confirmed by formation of a stable aqueous colloid with a Zeta potential of -29.5mV and the absence of voids in the particle-adhesive interface on the transmission electron microscopy images. The reported synthesis and functionalization process produced upconverting nanoparticles emitting photons within the blue spectral region (450 nm and 474 nm).